The Determinant of Banking Profitability in Indonesia (A Study of Commercial Banks Listed on the Indonesia Stock Exchange in 2013-2019) - Parhan, Muhammad (Jurnal Ilmiah Mahasiswa FEB, 2021)
This study aimed to analyze the effect of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), Operating Expense to Operating Income (BOPO), Loan to Deposit Ratio (LDR) on Banking Profitability (ROA) at commercial banks listed on the IDX in 2013-2019. There was a decline in the growth of third party funds and credit from 2013 to 2019 which had an effect on bank profitability. Therefore the authors are interested in taking the title determinants of profitability of commercial banks in Indonesia which are listed on the IDX. Data analysis technique used the panel data regression with a fixed effect model. The data used are secondary data in the form of published financial ratios with a total of 154 observations. The sample consisted of 22 banks which was conducted by means of purposive sampling. The results show that CAR has a positive and significant effect towards ROA. NPL has a negative and significant effect on ROA. NIM has an effect but not significant on ROA. BOPO has a negative and significant effect towards ROA. LDR has an effect but not significant on ROA. Simultaneously CAR, NPL, NIM, BOPO, and LDR have a significant effect on ROA of commercial banks listed on the IDX 2013-2019.Keywords: CAR, NPL, NIM, BOPO, LDR, ROA.